Nutritional Assessment Of Smoked Dried Fish Pre-Treated With Natural Spices - Linus-Chibuezeh, Adindu; Ndife, Joel; Adindu-Linus, Chidiamara; Nwodo, Catherine (Indonesian Food Science and Technology Journal, 2022)
This study is examined the effect of using different pretreatment methods on the quality of smoke-dried sardine fish. The fish samples were pretreated using salt, and some natural spices (cloves, nutmeg and yaji) prior to smoke drying. The proximate composition, minerals, physicochemical properties and microbial analysis of the fish samples were analyzed using standard analytical methods and data obtained were analyzed using ANOVA and significance accepted for P< 0.05. Result of proximate analysis showed a moisture range of 10.46 -37.20%, ash 13.81-17.57%, fat 5.81-9.24%, protein 37-46.31% and carbohydrate 5.57-26.74%. Mineral compositions (mg/100g) were in the range of 2.00 – 2.11 Mg, 25.25-25.85Ca, 14.40-14.55 potassium, 10.29-10.72 Na and iron ranged from 1.59-1.71. Low pH and TBA values obtained are indication that rancidity will not occur during storage. Bacteria and fungi count were 2.0 x 108 and 2.4 x 108 CFU/g respectively. The fish treated with Yaji and Brine was mostly preferred in all the sensory attributes. However, all samples differed with respect to overall acceptability.